ß-Hydroxy-ß-Methylbutyrate (HMB) as an ergogenic aid in sport - Slater, G. J. (International SportMed Journal, 2001)
ß-Hydroxy ß-methylbutyrate (HMB), a metabolite of the essential amino acid leucine, is a relatively new ergogenic aid proposed to influence skeletal-muscle protein metabolism and cell-membrane integrity. As with many new dietary supplements, relatively few investigations have been undertaken to critique claims of lean-body-mass gain, strength development, fat-mass loss, and suppression of exercise-induced skeletal-muscle damage. Furthermore interpretation of data from several investigations undertaken to date is difficult because of limitations in assessment techniques or lack of control over parameters that are liable to influence outcomes. Support for the ergogenic potential of HMB is at best inconsistent and transient, especially in previously trained individuals. The duration of administration in investigations undertaken to date, however, might be inadequate to enable identification of responses unique to HMB supplementation. Thus, longer-duration investigations using more precise monitoring techniques are warranted. Based on current evidence, athletes might be better advised to use other strategies that have proven to enhance performance.